On the influence of the temporal parameters of a new generalized sidelobe canceller receiver in a multipath environment - Ghanem, K.; Denidni, A.T. (Canadian Conference on Electrical and Computer Engineering 2004 (IEEE Cat. No.04CH37513), 2004)
The performance of tremendous beamforming methods degrades when the desired signal and interference are correlated. This correlation results primarily in signal cancellation. To overcome this drawback, signal processing techniques can be used. However, this implies increasing of the hardware or the software complexities without guaranteed enhancements. We address the performance of the new GSC receiver in non-coherent environments and it is shown to be viable especially at higher interference levels. The impact of the adaptive algorithm's parameters on the system performance is also investigated. Numerical simulations are provided and analyzed.